Why have all development strategies failed in Latin America? - Guillermo Rozenwurcel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
After the Great Depression and throughout the rest of the twentieth century, Latin American countries basically approached economic development following two successive and quite opposed strategies. The first one was import substitution industrialization. The second was the so-called Washington Consensus approach. While the two views were founded on quite opposite premises, neither the import substitution industrialization nor the Washington Consensus managed to deliver sustained economic development to Latin American countries. Two domestic elements are crucial to understand this outcome. One is the failure of the state. The second is the inability to achieve mature integration into the world economy.
Keywords: O11; O19; O54; O57; 330; Latin America; economic development; import substitution; role of the state; Entwicklungsstrategie; Importsubstitution; Wirtschaftspolitik; Wirkungsanalyse; Lateinamerika